MENGGAGAS COMPETITIVE ADVANTAGE MELALUI BRANDING IMAGE DI MADRASAH ALIYAH NURUL JADID PAITON PROBOLINGGO - Zainur Roziqin; Hefny Rozaq (Universitas Islam Negeri Ar-Raniry, 2018)
Choosing the best school is important for some people. the best school benchmark is a school that has a big name brand image in view of the majority of society. Lately more and more educational institutions are emerging, every institution is competing to improve the quality in order to win the competition. Schools that have a good image in the eyes of the public will win this competition. Therefore, brand image is an important thing that must be considered by education providers. This paper aims to determine the steps to form a brand image in Islamic Senior High School of Nurul Jadid Paiton Probolinggo as an effort to improve competitiveness. This study used a qualitative approach with the method of data mining in the form of observation, interview, and tracing of related documents.The results of this study indicate that there are several steps taken by Islamic Senior High School Of Nurul Jadid institution in forming brand image, which is institutional accreditation, inculcate good student behavior, improve student achievement, improve teacher quality and graduate quality, hold excellent activities, with alumni. These steps can improve competitiveness, with school accreditation, good graduate quality, student achievement, and student behavior have attracted the attention of the community to choose to continue their studies in Islamic Senior High School of Nurul Jadid, as well as being a challenge for other institutions.